2018
DOI: 10.1039/c8ce00099a
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization of varied calcium carbonate crystals by the synergistic effect of silk fibroin/magnesium ions in a microbial system

Abstract: The influence of silk fibroin (SF) and magnesium ions (Mg2+) on calcium carbonate (CaCO3) bio-mineralization has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Figure 1a shows a representative scanning electron microscopy (SEM) image of SrCO 3 particles which have a slightly spherical shape, obtained after a mineralization time of 6 h. Figure 1b shows dumbbell-like SrCO 3 obtained after a mineralization time of 12 h. Interestingly, with the increase of the mineralization time, the dumbbell-like SrCO 3 turned into popcorn-like SrCO 3 via the process of dissolution and recrystallization, see Figure 1c. By magnifying Figure 1c, we can clearly see that there are many voids left by the death of the bacteria on the surface of the SrCO 3 crystal, indicating that the microorganism acts as a nucleation site for SrCO 3 crystallization, which is consistent with the experimental results of Chen et al [24,25,26]. The change in the surface morphology could reflect the dissolution and recrystallization process of nano-spherical SrCO 3 .…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Figure 1a shows a representative scanning electron microscopy (SEM) image of SrCO 3 particles which have a slightly spherical shape, obtained after a mineralization time of 6 h. Figure 1b shows dumbbell-like SrCO 3 obtained after a mineralization time of 12 h. Interestingly, with the increase of the mineralization time, the dumbbell-like SrCO 3 turned into popcorn-like SrCO 3 via the process of dissolution and recrystallization, see Figure 1c. By magnifying Figure 1c, we can clearly see that there are many voids left by the death of the bacteria on the surface of the SrCO 3 crystal, indicating that the microorganism acts as a nucleation site for SrCO 3 crystallization, which is consistent with the experimental results of Chen et al [24,25,26]. The change in the surface morphology could reflect the dissolution and recrystallization process of nano-spherical SrCO 3 .…”
Section: Resultssupporting
confidence: 87%
“…The concentration of nano-MMT has a significant influence on the formation of SrCO 3 crystals with unique morphologies because nano-MMT determined the supersaturation of SrCO 3 in mineralized systems. The formation of flower-like SrCO 3 crystals may be attributed to the high concentration of nano-MMT which led to excessive accumulation of rod-like SrCO 3 crystals around the monolayer nano-MMT [26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, SF NPs with a large specific surface area exhibit outstanding aqueous stability and can serve as the sacrificial template or reductant for assembly of nanostructures. For instance, crystallization of CaCO 3 and MnO 2 can be achieved on the skeleton of SF via biomineralization-inspired metal reduction 30 , 31 . However, until now, no studies related to the synthesis of novel nanocatalyst through SF-mediated bioinspired crystallization have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicated that biomacromolecules were closely related to bioinspired mineralization process. For instance, the mineralization of CaCO 3 can be induced and regulated by SF-based nanostructures through an oriented crystallization process 26, 27. Therefore, controllable growth of inorganic substances on the skeleton of SF could be achieved by biomineralization-inspired metal reduction, rendering new possibilities of therapeutic-related functionalization of SF matrix.…”
Section: Introductionmentioning
confidence: 99%